Absorbable peripheral vascular stent for human body and preparation method of absorbable peripheral vascular stent

Through the three-layer structure of bioabsorbable peripheral vascular stent, combined with multi-layer coextrusion and laser engraving technology, the problems of excessive blood vessel burden and restenosis caused by metal stents in the prior art are solved, and the degradation time matching vascular repair and Effective drug release improves the safety and efficacy of treating peripheral vascular diseases.

CN119112436AInactive Publication Date: 2024-12-13JILIN UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411628008.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When treating peripheral vascular diseases, there is a risk of excessive vascular burden, long-term vascular stimulation and restenosis caused by metal stents, and the degradation rate of degradable metal stents does not match the time of vascular remodeling, and the local metal ion concentration is too high. Causes vascular inflammatory reaction.

Method used

Using a three-layer structure, the bioabsorbable peripheral vascular stent is made of bioabsorbable polyester material, the inner drug-loading layer is blended with anticoagulant drugs or chemically modified, the outer drug-loading layer is anti-inflammatory and promoting Endothelial drug blending or chemical modification, a stable stent structure is formed through multi-layer coextrusion technology and laser engraving process to ensure uniform distribution and effective release of drugs.

Benefits of technology

It provides a degradation time that matches vascular repair and healing, reduces the risk of restenosis, avoids complications of metal stents, ensures the biomechanical properties of the stent, anticoagulant and anti-inflammatory functions, and improves the safety of clinical applications and Effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119112436A_ABST
    Figure CN119112436A_ABST
Patent Text Reader

Abstract

The invention provides a human body absorbable peripheral vascular stent and a preparation method thereof, and belongs to the technical field of medical interventional instrument manufacturing, a human body absorbable high polymer material is adopted as a stent base material, the stent base material can be completely absorbed in vivo, and complications after a metal stent is implanted are avoided; through a blending or chemical modification method, an endothelialization promoting, anti-inflammatory and anticoagulant drug is combined with a polymer base material, so that the stability and effective release of the drug are ensured; the multi-layer co-extrusion technology ensures uniform distribution and good combination of all layers of materials, and a stable three-layer structure support is formed; laser engraving ensures that the bracket is manufactured more accurately; the stent adopts a three-layer structure design, respectively provides anti-inflammatory, endothelialization promotion and anticoagulation functions, and is helpful for reducing the risk of restenosis; the stent has good biomechanical properties and degradation time matched with vascular repair and healing, and is suitable for treatment of peripheral vascular diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a human body absorbable peripheral vascular stent. The present invention further discloses a preparation method of the human body absorbable peripheral vascular stent, which has the advantages of uniform material distribution, functional stratification, strong structural stability, high manufacturing precision, etc., and belongs to the technical field of medical interventional device manufacturing. Background Art

[0002] In the medical field, peripheral blood vessels include the vascular network leading to the thoracic, abdominal and pelvic organs, trunk and limbs, covering arteries, veins and capillaries. There is a big difference between peripheral blood vessels and coronary arteries in terms of vascular size. The diameter varies greatly, from the larger iliac artery (diameter can reach more than 10 mm) to the small capillaries (diameter is only about 5-10 microns), while the diameter of the coronary artery is relatively small, about 3-4 mm for the left coronary artery trunk and 2-3 mm for the right coronary artery. Peripheral vascular diseases are common diseases, including occlusive arteriosclerosis, Takayasu arteritis and occlusive vasculitis, with an incidence rate of up to 15% to 20%, and are often found in key peripheral small and medium arteries such as the iliac artery, renal artery, celiac artery, innominate artery, left common carotid artery, left subclavian artery, and femoral artery. These diseases have unique pathological characteristics, such as severe vascular occlusion, long diseased blood vessels with large caliber differences, and complex vascular stress caused by frequent joint activities.

[0003] At present, minimally invasive intravascular interventional surgery can be used to treat peripheral vascular diseases, usually using metal stents or the ends of the stents are often provided with exposed metal alloy areas. Although such stents can temporarily solve the problem, their application is limited by side effects such as long-term foreign body stimulation, limited vasoconstriction, stent thrombosis and restenosis. Although existing drug-coated stents can prevent restenosis, the problems of long-term vascular stimulation and restenosis have not been solved. Although much progress has been made in the research of degradable stents for coronary arteries, there have been no reports on the research of peripheral vascular stents with a diameter of 4-20 mm.

[0004] The braided vascular stent disclosed in patent CN 106073957A is designed with metal monofilament braiding and drug-loaded coating, but the non-degradability of metal may still lead to increased vascular burden and restenosis risk. Degradable metal stent materials such as Mg and Fe are degradable, but the limitations in degradation rate and performance limit their clinical promotion. The degradation rate of the degradable sustained-release drug-coated zinc alloy or magnesium alloy vascular stent disclosed in CN 114246992A does not match the time of vascular remodeling, and excessive local metal ion concentration can cause vascular inflammatory response.

[0005] Therefore, it is particularly important to develop a degradable polymer vascular stent for patients with peripheral vascular disease. This stent should have mechanical enhancement, a degradation time that matches the healing of blood vessels, and be able to promote vascular endothelialization and vascular remodeling, thereby effectively reducing the restenosis rate in the stent and providing stronger support for clinical applications. Summary of the invention

[0006] The present invention discloses a human body absorbable peripheral vascular stent and a preparation method thereof, which has uniform material distribution, functional stratification, strong structural stability, high manufacturing precision, excellent biomechanical properties, absorbability, anti-coagulation and promotion of vascular endothelialization, and a peripheral vascular stent that matches the vascular repair and healing time; it is used to solve the problems of excessive vascular burden, long-term vascular irritation and restenosis risks caused by metal stents, and the release of metal ions that easily cause local inflammatory reactions.

[0007] The method for preparing a human body absorbable peripheral vascular stent described in the present invention has the following technical solutions:

[0008] The middle layer is made of bioabsorbable polyester material and serves as the main part of the stent; the inner drug-loading layer is composed of a composite material obtained by blending or chemically modifying a bioabsorbable polyester material and an anticoagulant drug, and is used to provide an anticoagulant function; the outer drug-loading layer is composed of a composite material obtained by blending or chemically modifying a bioabsorbable polyester material and an anti-inflammatory and endothelialization-promoting drug, and is used to provide an anti-inflammatory and endothelialization-promoting function.

[0009] The method for preparing a human body absorbable peripheral vascular stent according to the present invention comprises the following steps:

[0010] The first step is to prepare the middle layer material; after drying the bioabsorbable polyester material, it is directly used in the multi-layer co-extrusion process of the stent; The second step is to prepare the inner drug-carrying layer material; the bioabsorbable polyester material and the anticoagulant drug are combined by blending or chemical modification at a mass ratio of 99:0.01-1; The third step is to prepare the external drug-loading layer material: the bioabsorbable polyester material is combined with the anti-inflammatory and endothelialization-promoting drugs at a mass ratio of 99:0.01-1 by blending or chemical modification; The fourth step is to add the inner drug-carrying layer material, the middle layer material and the outer drug-carrying layer material into three independent mixing kettles respectively, stir them at a high speed within a temperature range of 25°C to 60°C, and perform vacuum dehydration treatment to remove moisture; extrude them respectively to obtain the molten state of the inner drug-carrying layer material, the middle layer material and the outer drug-carrying layer material; transport the inner layer material, the middle layer material and the outer drug-carrying layer material to the corresponding flow channels of the multi-layer composite mold through pipelines, and use the multi-layer composite mold to perform multi-layer co-extrusion to form a round tube with a three-layer structure; the temperature of the mold is controlled between 150°C and 250°C; the extruded round tube is shaped by a sizing mold, and cooled and solidified by a cooling system, and the cooling temperature is controlled between 25°C and 45°C; The fifth step is to laser engrave the extruded round tube, put the round tube into the laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving, and finally obtain the finished stent; The second and third steps involve the following blending processes: dissolving the bioabsorbable polyester material and the drug molecules in dichloromethane, mixing them uniformly by ultrasonic or magnetic stirring, and controlling the temperature between room temperature and 50° C.; after the solvent evaporates, a solid blending material is formed; The chemical modification process involved in the second and third steps is: introducing amino or carboxyl groups into the bioabsorbable polyester material chain, and then using DCC and NHS as catalysts to carry out covalent bonding reactions in anhydrous dichloromethane. The reaction temperature is between room temperature and 50°C and lasts for 4-24 hours.

[0011] The thickness of the middle layer of the stent described in the present invention is 0.5-1.5 mm, the thickness of the outer drug-loaded layer is 0-0.5 mm, and the thickness of the inner drug-loaded layer is 0-0.5 mm; the outer diameter range of the stent is 1-30 mm to adapt to peripheral blood vessels of different sizes; the thickness range of the stent is 0.1-1.5 mm, and the length range is 10-100 mm to meet the needs of different lesion sites.

[0012] The stent of the present invention has n unit supports in the radial direction, where n is an integer ≥ 2, each having a length range of 1-20 mm, and a shape including V-shape, wave shape, rhombus shape, hexagonal shape or irregular polygon shape, and the shape is divided into crests and troughs; adjacent unit supports are connected by connectors, and the connection method includes crest-peak connection or crest-trough connection; the shape of the connector includes I-type, U-type, S-type, V-type, W-type, N-type or Ω-type and other arbitrary irregular shapes, which can increase the surface area of ​​the stent and facilitate the release of drugs and the attachment of vascular cells.

[0013] The bioabsorbable polyester monomer of the present invention is selected from: one or more blends of polylactic acid, polyglycolide, polydioxanone or polyε-caprolactone; the number average molecular weight of the bioabsorbable polyester material ranges from 300,000 to 600,000 Daltons, and the molecular weight distribution index ranges from 1.01 to 3.

[0014] During blending, two bioabsorbable polyester materials are blended at a mass ratio of 100:(0-100) or three different bioabsorbable polyester materials are blended at a mass ratio of 100:(0-100):(0-100) or four different bioabsorbable polyester materials are blended at a mass ratio of 100:(0-100):(0-100):(0-100); the blended materials are dissolved in a dichloromethane organic solvent, mixed evenly by ultrasonic or magnetic stirring, and the temperature is controlled between room temperature and 50°C; after the solvent evaporates, a uniformly distributed blended material is formed.

[0015] The anti-inflammatory and endothelialization promoting drug molecule monomers and their mass fractions in the outer drug-carrying layer of the present invention include but are not limited to: rapamycin (1×10⁻ 6 %-1×10⁻³%), RGD peptide (1×10⁻³%-1×10⁻²%), vascular endothelial growth factor (1×10⁻ 7 %-1×10⁻ 5 %), indomethacin (1×10⁻²%-4×10⁻¹%), flunarizine (1×10⁻ 6 %-1×10⁻³%), dexamethasone (1×10⁻ 4 %-1×10⁻²%), interleukin-10 (1×10⁻ 7 %-1×10⁻ 5 %), interferon-β (1×10⁻¹%-1×10 0 %), mitoxantrone (1×10⁻ 6 %-1×10⁻³%), atorvastatin (1×10⁻ 6 %-2×10⁻ 4 %), Qunis (1×10⁻ 7 %-1×10⁻ 6 %), squalene (1×10⁻ 4 %-4×10⁻³%), adenosine (2×10⁻ 5 %-2×10⁻³%), endothelin receptor antagonists (1×10⁻ 6 %-1×10⁻³%), angiogenin (1×10⁻ 7 %-1×10⁻ 5 %) and fibroblast growth factor (1×10⁻ 7 %-1×10⁻ 5 %) to provide anti-inflammatory and pro-endothelialization functions.

[0016] The degradable ester and anticoagulant drug molecular monomers and their mass fractions in the inner drug-carrying layer include, but are not limited to: heparin (1×10⁻ 6 %-1×10⁻ 4 %), antithrombin (1×10⁻ 6 %-1×10⁻³%), warfarin (1×10⁻ 6 %-1×10⁻³%), dabigatran (1×10⁻ 6 %-1×10⁻³%), rivaroxaban (1×10⁻ 6 %-1×10⁻³%), Apixaban (1×10⁻ 6 %-1×10⁻³%), Edoxaban (1×10⁻ 6 %-1×10⁻³%), Argaquban (1×10⁻ 6 %-1×10⁻³%), fondaparinux sodium (1×10⁻ 6 %-1×10⁻³%), naproxen (1×10⁻¹%-1×10 0 %), aspirin (2×10⁻²%-2×10⁻¹%), clopidogrel (1×10⁻ 6 %-1×10⁻³%), Prasugrel (1×10⁻ 6 %-1×10⁻³%), Ticagrelor (1×10⁻ 6 %-1×10⁻³%), eptifibatide (1×10⁻ 6 %-1×10⁻³%), tirofiban (1×10⁻ 6 %-1×10⁻³%), bevacizumab (1×10⁻ 5 %-1×10⁻²%) to provide anti-coagulation function.

[0017] The positive effects of the present invention are:

[0018] The preparation method provided adopts a polymer material absorbable by the human body as a stent substrate, which can be completely absorbed in the body to avoid complications after the implantation of the metal stent; by blending or chemical modification, endothelialization promoting, anti-inflammatory and anticoagulant drugs are combined with the polymer substrate to ensure the stability and effective release of the drugs; multi-layer co-extrusion technology ensures the uniform distribution and good combination of each layer of material to form a stable three-layer structure stent; laser engraving ensures more precise stent manufacturing; the stent adopts a three-layer structure design, which respectively provides anti-inflammatory, endothelialization promoting and anticoagulant functions, which helps to reduce the risk of restenosis; the stent has good biomechanical properties and a degradation time that matches vascular repair and healing, and is suitable for the treatment of peripheral vascular diseases. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1This is a schematic diagram of the structure of the human body absorbable peripheral vascular stent of the present invention; Figure 2 This is a scanning electron microscope image of the laser engraved absorbable vascular stent in Example 1 of the present invention; Figure 3 This is a schematic diagram of the parallel sinusoidal straight bridge open unit structure of the human body absorbable peripheral vascular stent in Example 1 of the present invention; Figure 4 The test results of the relationship between the time and the molecular weight change in the mixed solution in vitro degradation experiment of Example 1, Example 6 and Example 7; Figure 5 This is a graph showing the compression support force test data of the flat plate of Examples 1, 8, 9, 10 and 11 of the present invention; Figure 6 This is a schematic diagram of the structure of a parallel sinusoidal straight bridge closed unit of the human absorbable peripheral vascular stent according to Example 12 of the present invention; Figure 7 This is a schematic diagram of the parallel sinusoidal W-bridge closed unit structure of the human body absorbable peripheral vascular stent according to Example 13 of the present invention; Figure 8 This is a schematic diagram of the diamond structure of the human body absorbable peripheral vascular stent according to Example 14 of the present invention; Fig. 9 This is a graph showing the compression support force test data of the flat plate of Examples 1, 12, 13, and 14 of the present invention; Fig.10 Figure 12, 13, 14, and 15 of the present invention show the cell proliferation of human umbilical vein endothelial cells after culturing them in culture medium for 7 days; Fig.11 This is a picture of cell proliferation observed under a microscope during the biocompatibility test of Example 1 of the present invention; Fig.12 This is a picture of cell proliferation observed under a microscope during the biocompatibility test of Example 7 of the present invention; In the figure: 1. Inner drug-carrying layer; 2. Intermediate layer; 3. Outer drug-carrying layer; 4. Unit support body; 5. Straight bridge structure. DETAILED DESCRIPTION

[0020] The present invention is further described by way of the following examples, which do not limit the present invention in any way. Without departing from the technical solution of the present invention, any modification or change made to the present invention that is easily implemented by a person of ordinary skill in the art will fall within the scope of the claims of the present invention. Example 1

[0021] The first step is to prepare the middle layer material: 1000 g of L-polylactic acid (PLA) with a molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and heparin are mixed at a mass ratio of 99:1; the mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 99:1; the mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion machine to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion machine at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively; the material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process; the extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to put the multilayer tube into a laser engraving machine, and use the laser engraving machine to engrave the inner layer material, the middle layer material and the outer layer material to form an absorbable bare stent. The structural diagram is shown in Figure 1 As shown: inner drug-carrying layer 1; middle layer 2; outer drug-carrying layer 3; open unit structure as shown Figure 3 As shown: the unit support body 4 is parallel to the sine curve shape, the connector is a straight bridge structure 5, the length is 5 mm; the outer diameter of the sine curve arc of the unit support body 4 is 1.5 mm, the inner diameter of the sine curve arc is 0.5 mm, and the amplitude of the sine curve is 10 mm; the scanning electron microscope image of the laser engraved absorbable vascular stent is as shown Figure 2 As shown; Biocompatibility test cell proliferation observation under microscope as shown Fig.11 shown. Example 2

[0022] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-carrying layer: mix L-polylactic acid and heparin at a mass ratio of 99:1, and use chemical modification technology to prepare a composite material; introduce amino or carboxyl active groups on the L-polylactic acid chain, and then modify the heparin into a succinic anhydride derivative. Use N,N'-dicyclohexylcarbodiimide as a catalyst, react in anhydrous dichloromethane, control the temperature at 50°C, and react for 12 hours; after the reaction is completed, remove the unreacted reagents and residual substances by ultrafiltration to obtain the inner drug-carrying layer material; The third step is to prepare the external drug-carrying layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 999:1; rapamycin is first modified into a reactive form, and N,N'-dicyclohexylcarbodiimide is used as a catalyst to react with L-polylactic acid in anhydrous dichloromethane: the reaction temperature is controlled at 50°C, and the reaction time is 12 hours: after the reaction, the residual substances are removed by ultrafiltration to obtain the external drug-carrying layer material; The fourth step is to prepare a hollow round tube with a three-layer structure by using a multi-layer co-extrusion tube extruder: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are simultaneously fed into the multi-layer co-extrusion tube extruder in a ratio of 2:6:2; the co-extruder is equipped with an independent heating zone and a screw system to control the temperature, pressure and flow rate of each layer of material respectively; the material is fully melted at a temperature of 180°C and a compact three-layer structure is formed during the extrusion process; the extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal unit support and a straight bridge-shaped connector structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the sinusoidal amplitude is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 3

[0023] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-carrying layer: mix L-polylactic acid and heparin in a mass ratio of 99:1, and use chemical modification technology to prepare a composite material. Introduce amino or carboxyl active groups on the L-polylactic acid chain, and then modify the heparin into a succinic anhydride derivative; use N,N'-dicyclohexylcarbodiimide as a catalyst, react in anhydrous dichloromethane, control the temperature at 50°C, and react for 12 hours; after the reaction is completed, remove the unreacted reagents and residual substances by ultrafiltration to obtain the inner drug-carrying layer material; The third step is to prepare the external drug-carrying layer: mix L-polylactic acid and rapamycin in a mass ratio of 99:1. First, modify rapamycin into a reactive form, use N,N'-dicyclohexylcarbodiimide as a catalyst to react with L-polylactic acid in anhydrous dichloromethane; control the reaction temperature at 50°C and the reaction time for 12 hours; after the reaction, remove the residual substances by ultrafiltration to obtain the external drug-carrying layer material; The fourth step is to prepare a hollow round tube with a three-layer structure by using a multi-layer co-extrusion tube extruder; the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are simultaneously fed into the multi-layer co-extrusion tube extruder in a ratio of 3:6:1; the co-extruder is equipped with an independent heating zone and a screw system to control the temperature, pressure and flow rate of each layer of material respectively; the material is fully melted at a temperature of 180°C and a compact three-layer structure is formed during the extrusion process; the extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent open unit with a sinusoidal and straight bridge-shaped open unit structure; there are 6 absorbable bare stent open units, and the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 4

[0024] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-carrying layer: mix L-polylactic acid and heparin in a mass ratio of 99:1, and use chemical modification technology to prepare a composite material. Introduce amino or carboxyl active groups on the L-polylactic acid chain, and then modify the heparin into a succinic anhydride derivative; use N,N'-dicyclohexylcarbodiimide as a catalyst, react in anhydrous dichloromethane, control the temperature at 50°C, and react for 12 hours; after the reaction is completed, remove the unreacted reagents and residual substances by ultrafiltration to obtain the inner drug-carrying layer material; The third step is to prepare the external drug-carrying layer: mix L-polylactic acid and rapamycin in a mass ratio of 99:1. First, modify rapamycin into a reactive form, use N,N'-dicyclohexylcarbodiimide as a catalyst to react with L-polylactic acid in anhydrous dichloromethane; control the reaction temperature at 50°C and the reaction time for 12 hours; after the reaction, remove the residual substances by ultrafiltration to obtain the external drug-carrying layer material; The fourth step is to use a multi-layer co-extrusion machine to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion machine at the same time in a ratio of 1:8:1; the co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material. The material is fully melted at a temperature of 180°C and forms a tight three-layer structure during the extrusion process; the extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 5

[0025] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-carrying layer: L-polylactic acid and heparin are mixed at a mass ratio of 99:1, and a composite material is prepared by chemical modification technology; amino or carboxyl active groups are introduced into the L-polylactic acid chain, and then the heparin is modified into a succinic anhydride derivative; N,N'-dicyclohexylcarbodiimide is used as a catalyst, and the reaction is carried out in anhydrous dichloromethane, the temperature is controlled at 50°C, and the reaction time is 12 hours; after the reaction is completed, the unreacted reagents and residual substances are removed by ultrafiltration to obtain the inner drug-carrying layer material; The third step is to prepare the external drug-carrying layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 99:1; rapamycin is first modified into a reactive form, and N,N'-dicyclohexylcarbodiimide is used as a catalyst to react with L-polylactic acid in anhydrous dichloromethane; the reaction temperature is controlled at 50°C and the reaction time is 12 hours; after the reaction, the residual substances are removed by ultrafiltration to obtain the external drug-carrying layer material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 1:6:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 6

[0026] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 200,000 Daltons and a molecular weight distribution of 2.5 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and heparin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion machine to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion machine at the same time in a ratio of 3:4:3; the co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material. The material is fully melted at a temperature of 180°C and forms a tight three-layer structure during the extrusion process; the extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 7

[0027] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 50,000 Daltons and a molecular weight distribution of 2.5 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and heparin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm.

[0028] For Example 1, Example 6, and Example 7, a solution-simulated in vitro degradation experiment was conducted. The samples were placed in a phosphate buffer solution, the pH value of which was 7. The solution was replaced every 5 days to maintain a stable pH value. The experiment was conducted at 25° C. Every 5 days, a portion of the scaffold material was taken for molecular weight determination using gel permeation chromatography to determine its degradation state. Figure 4 As shown; the test results of the relationship between the time and molecular weight change of the mixed solution in vitro degradation experiment are shown in Fig.12 ; The degradation rate is highly matched with the vascular healing time. The stent provides the necessary support in the early stage and then gradually degrades, ensuring that the stent can be absorbed after the vascular healing is completed, reducing long-term complications. The monitoring results of molecular weight changes show that the degradation process is uniform and controllable, ensuring that the stent maintains stable mechanical properties during the degradation process. Example 8

[0029] The first step is to prepare the middle layer material: the absorbable polyester material is polydioxanone; 1000 grams of polydioxanone with a number average molecular weight of 80,000 Daltons and a molecular weight distribution of 1.3 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: polydioxanone and heparin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; Step 3: Prepare the outer drug-loaded layer: Mix polydioxanone and rapamycin at a mass ratio of 99:1. Dissolve the mixture in dichloromethane, stir it evenly by magnetic stirring, and then remove the solvent by solvent evaporation to obtain a uniformly distributed drug-loaded material. The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 9

[0030] The first step is to prepare the middle layer material: select the absorbable polyester material as poly-ε-caprolactone; put 1000 grams of poly-ε-caprolactone with a number average molecular weight of 30,000 Daltons and a molecular weight distribution of 1.1 into a 70°C oven for drying; The second step is to prepare the inner drug loading layer: poly-ε-caprolactone and heparin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug loading material; Step 3: Prepare the outer drug-loaded layer: Mix poly-ε-caprolactone and rapamycin at a mass ratio of 99:1. Dissolve the mixture in dichloromethane, stir it evenly by magnetic stirring, and then remove the solvent by solvent evaporation to obtain a uniformly distributed drug-loaded material. The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 10

[0031] The first step is to prepare the middle layer material: the absorbable polyester material is selected as a mixture of low molecular weight L-polylactic acid and poly-ε-caprolactone, the ratio of low molecular weight L-polylactic acid: poly-ε-caprolactone = 80:20, and the mixture is placed in a 70°C oven for drying; The second step is to prepare the inner drug loading layer: a mixture of L-polylactic acid and poly-ε-caprolactone is mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug loading material; The third step is to prepare the outer drug-loading layer: a mixture of L-polylactic acid and poly-ε-caprolactone is mixed with rapamycin at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3; the co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm. The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Embodiment 11

[0032] The first step is to prepare the middle layer material: the absorbable polyester material is selected as a mixture of low molecular weight L-polylactic acid, polydioxanone and poly-ε-caprolactone, the ratio of low molecular weight L-polylactic acid: polydioxanone: poly-ε-caprolactone = 60:20:20, and the mixture is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: a mixture of L-polylactic acid, polydioxanone and poly-ε-caprolactone is mixed with heparin at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; Step 3: Prepare the outer drug-loading layer: mix a mixture of L-lactic acid, polydioxanone and poly-ε-caprolactone with rapamycin at a mass ratio of 99:1. Dissolve the mixture in dichloromethane, stir it evenly by magnetic stirring, and then remove the solvent by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to ensure the structural integrity and dimensional stability of the stent; a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm is formed; The fifth step is to put the multilayer tube into a laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form an absorbable bare stent with a quasi-sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm; The bare stents prepared in Examples 1, 8, 9, 10, and 11 were subjected to a flat plate extrusion support force test. The test instrument was a WSM-20kN electronic universal material testing machine. During the test, the stent was compressed at a rate of 5 mm / min. The stent to be tested was placed between the chuck plates of the tensile testing machine. The upper and lower chucks of the tensile testing machine were manually adjusted to compress it. The compression increment was 1 mm, and the support force was recorded. The test results are shown in the attached figure. Figure 5As shown. The multi-layer co-extrusion technology ensures the uniform distribution and reasonable combination of materials, giving the stent excellent compressive resistance and mechanical properties; the laser engraving process optimizes the grid structure of the stent with its high precision, giving it better flexibility and radial support. In addition, the material selection and ratio of the stent are carefully designed to ensure that the stent is gradually degraded and absorbed in the body while maintaining durability and stability. These processes enable the stent to effectively maintain the patency of blood vessels in actual clinical practice, reduce the risk of restenosis, and improve the overall efficacy. Example 12

[0033] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and heparin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to ensure the structural integrity and dimensional stability of the stent. A multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm is formed; The fifth step is to put the multilayer tube into the laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form an absorbable bare stent with a quasi-sinusoidal and straight bridge-shaped open unit structure; a quasi-sinusoidal and straight bridge-shaped closed unit structure (see Figure 6 As shown), the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Embodiment 13

[0034] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and heparin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C; a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm is formed; The fifth step is to put the multilayer tube into the laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form an absorbable bare stent with a quasi-sinusoidal and straight bridge-shaped closed unit structure; a quasi-sinusoidal and W-shaped straight bridge structure open unit structure, the bridge wire diameter of the W-shaped straight bridge structure is the same as the wall thickness of the absorbable polyester tube, which is 1 mm; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the sinusoidal amplitude is 10 mm, and the diameter of the W-shaped straight bridge structure is 2.5 mm (see Figure 7 as shown). Embodiment 14

[0035] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and heparin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and rapamycin are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; Step 5: Place the multilayer tube into a laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form an absorbable bare stent with a rhombus structure; the side length of the rhombus is 10 mm, and the angle of each rhombus angle is 60 degrees, see Figure 8 As shown; the node of the unit support body 4 is the straight bridge structure 5.

[0036] The bare stents prepared in Examples 11, 12, 13, and 14 were subjected to a flat plate extrusion support force test. The testing instrument was a WSM-20kN electronic universal material testing machine. During the test, the stent was compressed at a rate of 1 mm / min. The stent to be tested was placed between the chuck plates of the tensile testing machine. The upper and lower chucks of the tensile testing machine were manually adjusted to compress it. The compression increment was 1 mm, and the support force was recorded. The test results are shown in the attached figure. Fig. 9 .

[0037] Through multi-layer co-extrusion technology, the stent material is evenly distributed in each layer, and combined with high-precision laser engraving technology, the V-shaped, W-shaped and diamond-shaped grid structures of the stent can be precisely formed. This process not only enhances the structural stability of the stent, but also optimizes its radial support force, so that the stent can effectively disperse stress when compressed and reduce the risk of breakage caused by local stress concentration. In particular, changes in shape design, such as diamond and wavy structures, give the stent higher flexibility and compressive resistance, allowing it to better adapt to changes in blood vessel morphology. In addition, through process control, the thickness, size and shape of the stent are precisely regulated, thereby ensuring that it still maintains sufficient mechanical support during its degradation process in the body. These shape and process optimizations enable the stent to exhibit better mechanical properties in clinical applications, effectively reduce the probability of restenosis, and improve the long-term stability and efficacy of the stent. Embodiment 15

[0038] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and rivaroxaban are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring. The solvent is then removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and RGD peptide are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Example 16

[0039] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and aspirin are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loading layer: L-polylactic acid and vascular endothelial growth factor are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Embodiment 17

[0040] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and clopidogrel are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring. Then, the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; The third step is to prepare the outer drug-loaded layer: L-polylactic acid and dexamethasone are mixed at a mass ratio of 99:1. The mixture is also dissolved in dichloromethane, mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to obtain a uniformly distributed drug-loaded material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm. Embodiment 18

[0041] The first step is to prepare the middle layer material: 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70°C oven for drying; The second step is to prepare the inner drug-loading layer: L-polylactic acid and tirofiban are mixed at a mass ratio of 99:1. The mixture is dissolved in an organic solvent, dichloromethane, and mixed evenly by magnetic stirring, and then the solvent is removed by solvent evaporation to form a uniformly distributed drug-loading material; Step 3: Prepare the outer drug-loading layer: mix L-polylactic acid and adenosine at a mass ratio of 99:1. Dissolve the mixture in dichloromethane, stir it evenly by magnetic stirring, and then remove the solvent by solvent evaporation to obtain a uniformly distributed drug-loading material; The fourth step is to use a multi-layer co-extrusion tube extruder to prepare a three-layer hollow round tube: the middle layer material, the inner drug-loaded layer material and the outer drug-loaded layer material are fed into the multi-layer co-extrusion tube extruder at the same time in a ratio of 3:4:3. The co-extruder is equipped with an independent heating zone and screw system to control the temperature, pressure and flow rate of each layer of material respectively. The material is fully melted at a temperature of 180°C and a tight three-layer structure is formed during the extrusion process. The extruded round tube is precisely sized by a sizing die and cooled and solidified in a cooling system at 45°C to form a multi-layer tube with an outer diameter of 10 mm, a wall thickness of 1 mm and a length of 70 mm; The fifth step is to place the multilayer tube into a laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving to form an absorbable bare stent with a sinusoidal and straight bridge-shaped open unit structure; the absorbable bare stent has 6 open units, the outer diameter of the sinusoidal arc of the unit support body 4 is 1.5 mm, the inner diameter of the sinusoidal arc is 0.5 mm, the amplitude of the sinusoidal curve is 10 mm, and the length of the straight bridge structure 5 is 5 mm.

Claims

1. A method for preparing a peripheral vascular stent that can be absorbed by the human body, characterized in that: The middle layer is made of bioabsorbable polyester material, serving as the main part of the stent; the inner drug-loading layer is composed of a composite material obtained by blending or chemically modifying a bioabsorbable polyester material and an anticoagulant drug, and is used to provide an anticoagulant function; the outer drug-loading layer is composed of a composite material obtained by blending or chemically modifying a bioabsorbable polyester material and an anti-inflammatory and endothelialization-promoting drug, and is used to provide an anti-inflammatory and endothelialization-promoting function; Specific preparation method The following steps are involved: The first step is to prepare the middle layer material; after drying the bioabsorbable polyester material, it is directly used in the multi-layer co-extrusion process of the stent; The second step is to prepare the inner drug-carrying layer material; the bioabsorbable polyester material and the anticoagulant drug are combined by blending or chemical modification at a mass ratio of 99: (0.01-1); The third step is to prepare the external drug-loading layer material: the bioabsorbable polyester material is combined with the anti-inflammatory and endothelialization-promoting drugs at a mass ratio of 99: (0.01-1) by blending or chemical modification; Step 4: Add the inner drug-carrying layer material, the middle layer material and the outer drug-carrying layer material into three separate mixing kettles respectively, stir them at a high speed in a temperature range of 25° C. to 60° C., and perform vacuum dehydration treatment to remove moisture; Extrusion molding is performed separately to obtain the molten state of the inner drug-carrying layer material, the middle layer material and the outer drug-carrying layer material; the inner layer material, the middle layer material and the outer drug-carrying layer material are transported to the corresponding flow channels of the multi-layer composite mold through a pipeline, and the multi-layer composite mold is used for multi-layer co-extrusion to form a round tube with a three-layer structure; the temperature of the mold is controlled between 150° C. and 250° C.; the extruded round tube is shaped by a sizing mold, and is cooled and solidified by a cooling system, and the cooling temperature is controlled between 25° C. and 45° C.; The fifth step is to laser engrave the extruded round tube, put the round tube into the laser engraving machine, and import the bare stent structure information file into the laser engraving machine for engraving, and finally obtain the finished stent; The second and third steps involve the following blending processes: dissolving the bioabsorbable polyester material and the drug molecules in dichloromethane, mixing them uniformly by ultrasonic or magnetic stirring, and controlling the temperature between room temperature and 50° C.; after the solvent evaporates, a solid blending material is formed; The chemical modification process involved in the second and third steps is: introducing amino or carboxyl groups into the bioabsorbable polyester material chain, and then using DCC and NHS as catalysts to carry out covalent bonding reactions in anhydrous dichloromethane. The reaction temperature is between room temperature and 50°C and lasts for 4-24 hours.

2. The method for preparing a peripheral vascular stent absorbable by the human body as claimed in claim 1, characterized in that: The bioabsorbable polyester monomer is selected from: one or more blends of polylactic acid, polyglycolide, polydioxanone or poly-ε-caprolactone; the number average molecular weight of the bioabsorbable polyester material ranges from 300,000 to 600,000 Daltons, and the molecular weight distribution index ranges from 1.01 to 3; When blending, two bioabsorbable polyester materials are blended at a mass ratio of 100:(0~100) or three different bioabsorbable polyester materials are blended at a mass ratio of 100:(0~100):(0~100) or four different bioabsorbable polyester materials are blended at a mass ratio of 100:(0~100):(0~100):(0~100); the blended materials are dissolved in a dichloromethane organic solvent, mixed evenly by ultrasonic or magnetic stirring, and the temperature is controlled between room temperature and 50°C; after the solvent evaporates, a uniformly distributed blended material is formed.

3. The stent prepared by the preparation method according to claim 1, characterized in that: The outer diameter of the stent is in the range of 1 to 30 mm, the thickness is in the range of 0.1 to 1.5 mm, and the length is in the range of 10 to 100 mm.

4. The stent produced by the preparation method according to claim 1, characterized in that: The thickness of the middle layer of the stent is 0.5-1.5 mm, the thickness of the outer drug-carrying layer is 0-0.5 mm, and the thickness of the inner drug-carrying layer is 0-0.5 mm.

5. The stent prepared by the preparation method according to claim 1, characterized in that: The radial direction of the stent is n unit supports, where n is an integer ≥ 2, each of which has a length range of 1-20 mm, and has a shape including V-shape, wave shape, diamond shape, hexagonal shape or irregular polygon shape, and the shape is divided into crests and troughs; adjacent unit supports are connected by connectors, and the connection methods include crest-to-crest connection or crest-to-trough connection; the shape of the connector includes I-type, U-type, S-type, V-type, W-type, N-type or Ω-type.

6. The stent produced by the preparation method according to claim 1, characterized in that: The anti-inflammatory and endothelialization-promoting drugs in the outer drug-carrying layer include, but are not limited to, rapamycin, RGD peptide, vascular endothelial growth factor, indomethacin, flunarizine, dexamethasone, interleukin-10, interferon-β, mitoxantrone, atorvastatin, tronisin, tert-squalene, adenosine, endothelin receptor antagonist, angiogenin and fibroblast growth factor.

7. The stent produced by the preparation method according to claim 1, characterized in that: The anticoagulant drugs in the inner drug-carrying layer include, but are not limited to, heparin, antithrombin, warfarin, dabigatran, rivaroxaban, apixaban, edoxaban, argetroban, fondaparinux sodium, naproxen, aspirin, clopidogrel, prasugrel, ticagrelor, eptifibatide, tirofiban, and bevacizumab.

Citation Information

Patent Citations

  • Novel knitted intravascular stent

    CN106073957A

  • Degradable intravascular stent with sustained-release drug coating and preparation method of degradable intravascular stent

    CN114246992A

  • Multilayered composite tube, manufacturing method thereof, and application thereof

    CN102552992A

  • Full-degradable vascular stent for vascular disease treatment and production method of full-degradable vascular stent

    CN106039425A

  • Artificial blood vessel and preparation method thereof

    CN109009561A